2016
DOI: 10.1590/s0102-865020160110000007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an experimental model of progressive renal disease in rats

Abstract: . Conception and design of the study, interpretation of data, statistical analysis, histopathological examinations, manuscript preparation and writing, critical revision, final approval. ABSTRACT PURPOSE:To characterize an experimental model of progressive renal disease induced by different degrees of nephrectomy in rats. METHODS:Eighty male Wistar rats were divided into four experimental groups (n=20/group): sham surgery (control group), progressive degrees of nephrectomy leading to mild uremia (group 1), mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
2
5
0
1
Order By: Relevance
“…This was also confirmed by histopathology and immunohistochemistry of α-SMA in which moderate glomerular hypertrophy with interstitial fibrosis was observed. Similar to the current study, hypertrophy of remnant glomeruli, mesangial expansion, increased glomerular collagen deposition in mice with 5/6 nephrectomy (Gava et al 2012), and tubulointerstitial changes in rats with subtotal nephrectomy were observed (Devada et al 2012 andBaracho et al 2016). In dogs, CKD induction resulted in stable chronic renal failure until 9-12 months (Vaneerdeweg et al 1992), high serum creatinine concentration which was 4.3±1.5mg/dL (Steiner et al 2010), mesangial hyperplasia, and focal glomerular sclerosis (Bourgoignie et al 1987).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This was also confirmed by histopathology and immunohistochemistry of α-SMA in which moderate glomerular hypertrophy with interstitial fibrosis was observed. Similar to the current study, hypertrophy of remnant glomeruli, mesangial expansion, increased glomerular collagen deposition in mice with 5/6 nephrectomy (Gava et al 2012), and tubulointerstitial changes in rats with subtotal nephrectomy were observed (Devada et al 2012 andBaracho et al 2016). In dogs, CKD induction resulted in stable chronic renal failure until 9-12 months (Vaneerdeweg et al 1992), high serum creatinine concentration which was 4.3±1.5mg/dL (Steiner et al 2010), mesangial hyperplasia, and focal glomerular sclerosis (Bourgoignie et al 1987).…”
Section: Discussionsupporting
confidence: 87%
“…Mild injury of the right kidney was confirmed by abdominal ultrasonography, histopathology, weak expression of α-SMA marker in the interstitial tissue and low expression of KIM-1 gene and NGAL gene which are sensitive and specific biomarkers of kidney injury (Rees and Kain 2008;Yin and Wang 2016). Similarly, a previous study on rats showed that the degree of impairment was directly related to the severity of the renal excision (Baracho et al 2016).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Additional in vivo models of differing degrees of uraemia can be achieved through the use of an adenine rich diet [43] or a varied surgical approach as described by Baracho et al [44]. At the time of designing our experiments, there were no studies which examined a shorter duration of uraemia, reflecting earlier stage kidney disease, where the response of the vasculature will be different to that of more advanced kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, the 5/6 nephrectomy was considered a good model for chronic kidney diseases. It was applied successfully in rats [ 14 , 15 ] and recently in dogs [ 16 ]. Few preclinical studies address the use of stem cells in large animal kidney injuries.…”
Section: Introductionmentioning
confidence: 99%